2005
DOI: 10.1111/j.0013-9580.2005.45004.x
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical and EEG Study on Idiopathic Partial Epilepsies with Evolution into ESES Spectrum Disorders

Abstract: Summary:Purpose: Questioning the presence of any possible prognostic predictors, this study includes a long-term follow-up of clinical and EEG characteristics of 16 patients with idiopathic partial epilepsy (IPE) who subsequently developed epilepsy with electrical status epilepticus during slow sleep (ESES) spectrum disorders.Methods: Epilepsy, cognitive and behavioral parameters, and waking and non-rapid eye movement (NREM) EEG data were evaluated and scored for initial stage (i.e., IPE stage), preESES, ESES,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
106
2
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(121 citation statements)
references
References 9 publications
7
106
2
6
Order By: Relevance
“…Other reports have shown that patients with a previous diagnosis of idiopathic partial epilepsy account for about one-third of the Electrical Status ES-ES cases (Saltik et al, 2005;Kramer et al, 2009).…”
Section: History and Etiology Of Esesmentioning
confidence: 96%
See 2 more Smart Citations
“…Other reports have shown that patients with a previous diagnosis of idiopathic partial epilepsy account for about one-third of the Electrical Status ES-ES cases (Saltik et al, 2005;Kramer et al, 2009).…”
Section: History and Etiology Of Esesmentioning
confidence: 96%
“…Similarly, Tassinari et al (2012) relies on the secondary bilateral synchrony mechanism which was assumed to work classically (Tükel and Jasper, 1952) by involving secondarily thalamic and thalamo-cortical circuitry. However, asymmetric, unilateral, or more focal/regional discharges were frequently reported (Bureau, 1995;Saltik et al, 2005;Van Hirtum-Das et al, 2006;Kramer et al, 2009;Liukkonen et al, 2010;Sánches Fernández et al, 2012). The sleep discharges in LKS were also found almost always asymmetric, with a dominant hemispheric and regional distribution congruently to the language disturbances.…”
Section: Terminological and Conceptual Chaos Around Eses Cswsmentioning
confidence: 99%
See 1 more Smart Citation
“…22 LKS may cause prolonged and severe loss of linguistic ability due to its impact on language areas. However, it became widely recognized when pediatric neurologists and psychiatrists realized the fact that there is a high percentage of the autism children might have a language and social deterioration in their past medical history.…”
Section: 18mentioning
confidence: 99%
“…Saltik и соавт. [34] показали, что имеется ряд клини-ческих признаков, которые могут указывать на появление ESES при идиопатических фокальных эпилепсиях: увели-чение частоты приступов, появление новых типов присту-пов, развитие когнитивных и поведенческих нарушений, нарастание изменений на ЭЭГ. В группе наблюдавшихся ими 16 пациентов детского возраста расстройства поведе-ния и психические нарушения имели место у 81% (13 из 16) и включали тревогу, депрессию, отвлекаемость, гипер-активность, импульсивность, повышенную раздражи-тельность.…”
Section: журнал неврологии и психиатрии 3 2016 обзорыunclassified